Tinjauan Hukum Terhadap Kedudukan Fatwa Dewan Syariah MUI dalam Usaha Asuransi di Indonesia - Muslim, Shohib; Hadiwinata, Khrisna (Qolamuna : Jurnal Studi Islam, 2018)
The purpose of this study to analyze the regulation that regulates the strength of the law of the national sharia board fatwa MUI Number 21/DSN-MUI/X/2001 on the implementation of sharia insurance business in Indonesia and to analyze how protection of the law against the insured in case of insolvency of sharia insurance company. The results of the research indicate that the legal force of the fatwa of the MUI Sharia Council is still very weak, so there is a need for a law-level regulation to accommodate the implementation of sharia insurance in Indonesia. Based on TAP MPR Number III/2000 regarding the source of National Law and Order of Regulation of the Unitary State of the Republic of Indonesia and the Law of the Republic of Indonesia Number 12 of 2012 on the Establishment of Laws and Regulations, the fatwa does not also include the type of state legislation Unity of the Republic of Indonesia. Keywords: Sharia Insurance, The Board’s fatwa MUI, Legal Protection.